Hypobaric Decompression Sickness Treatment Model - Conkin, Johnny; Abercromby, Andrew F J; Dervay, Joseph P; Feiveson, Alan H; Gernhardt, Michael L; Norcross, Jason R; Ploutz-Snyder, Robert; Wessel, 3rd, James H (Aerospace medicine and human performance, 2015)
The Hypobaric Decompression Sickness (DCS) Treatment Model links a decrease in computed bubble volume from increased pressure (ΔP), increased oxygen (O2) partial pressure, and passage of time during treatment to the probability of symptom resolution [P(SR)]. The decrease in offending volume is realized in two stages: 1) during compression via Boyles law; and 2) during subsequent dissolution of the gas phase via the oxygen window. We established an empirical model for the P(SR) while accounting for multiple symptoms within subjects. The data consisted of 154 cases of hypobaric DCS symptoms with ancillary information from tests on 56 men and 18 women. Our best estimated model is P(SR)=1/(1+exp(-(ln(ΔP)-1.510+0.795×AMB-0.00308×Ts)/0.478)), where ΔP is pressure difference (psid); AMB=1 if ambulation took place during part of the altitude exposure, otherwise AMB=0; and Ts is the elapsed time in minutes from the start of altitude exposure to recognition of a DCS symptom. Values of ΔP as inputs to the model would be calculated from the Tissue Bubble Dynamics Model based on the effective treatment pressure: ΔP=P2-P1|=P1×V1/V2-P1, where V1 is the computed volume of a bubble at low pressure P1 and V2 is computed volume after a change to a higher pressure P2. If 100% ground-level oxygen was breathed in place of air, then V2 continues to decrease through time at P2 at a faster rate.